Spatial Vortices in The Qur’an and Modern Science - Anjab, Sayed Najibullah (Integrated Journal for Research in Arts and Humanities, 2024)
Atmospheric vortices are one of the new issues that have attracted the attention of scientists today. The Holy Qur'an refers to atmospheric vortices in the first verse of Surah Takweer as the extinguishing and wrapping of the sun, in the eighth verse of Surah Qayamat as the dimming of the moon, in the first verse of Surah Najm, the eighth verse of Surah Mursalat and the second verse of Surah Infatar is mentioned as fading, darkening and scattering and collapsing of heavenly lights and stars. One of the types of death of stars is turning into vortices and black holes; Vortices are one of the most important astronomical phenomena that occur after the death of large stars. Vortices and black holes are the strangest objects in the world that do not reflect any light and do not bring us information; In addition, most vortices and black holes are the last stage of life of the brightest stars in the world; The main goal of this research is to explain the existence of the problem of spatial vortices in the Qur'an and compare it with modern science. What adds to the importance of this research is encouraging readers and researchers of today's world to study the Holy Quran and inviting them to discuss the issues of the day. The chosen method in this research is a library and analytical one, which first quotes Quranic verses from authentic books of interpretations and other books of modern science, then analyzes those verses and the ideas of scientists and the works and benefits derived from it. And it has been pointed out.